The Challenges of Elementary Education in Society 5.0 Era - Supa'at, Supa'at; Ihsan, Ihsan (International Journal of Social Learning (IJSL), 2023)
This study aims to describe the teachers’ perceptions and readiness to face classroom instruction in the eras of Industrial Revolution 4.0 and Society 5.0. As an essential part of education, teachers are responsible for teaching (imparting knowledge to students) and educating them (shaping their character traits). These roles demand the design of a learning process that stimulates students to acquire 21st-century skills. The challenges posed by the disruptive era of Industrial Revolution 4.0 and Society 5.0 (supersmart society era) present significant hurdles for today’s teachers. To address these challenges, teachers demonstrate adaptability and embrace ongoing development. This study employed a qualitative descriptive method to gather data; the data were collected through observation, interviews, document review, and secondary data sources. The study's primary respondents were 15 teachers from schools/madrassas (Islamic schools) in 5 regencies; Kudus, Pati, Rembang, Grobogan, and Blora. The results reveal that technological devices, learning methods, and human resources are the most significant barriers for teachers facing the society 5.0 era. To overcome these challenges, teachers must develop professional competencies in utilizing digital technology during classroom instruction.